Air navigation in high latitudes - Hagger, A. J. (Polar Record, 1950)
Near the Poles, the geographical system of reference by meridians and parallels approaches limiting conditions, and the apparent motion of heavenly bodies is unfamiliar. Accepted routines of navigation break down, and it is therefore necessary to devise new methods for the use of aircraft in polar regions. In addition, the weakness of the magnetic field in these regions forces us to modify or supplement the ordinary method of steering by magnetic compass. It cannot be too much emphasised, however, that the overriding criteria by which any technique must be examined are those which are common to navigation in all latitudes, and which are imposed by the nature of the aircraft itself. They arise chiefly owing to the speed and instability of the machine, and to the conditions of physical and mental strain in which the aerial navigator must work. Techniques and instruments must survive the three-fold test, applicable to any latitude: “Is the manipulative process handy enough to be done accurately by a navigator, tired or under nervous tension?”, “Is it simple enough for him to avoid errors under conditions of stress or mild anoxia?”, and “Is it fast enough?”